Beyond magenta : transgender teens speak out - Kuklin, Susan (Somerville, Massachusetts : Candlewick Press, 2014)
Shares insights into the teen transgender experience, tracing six individual's emotional and physical journey as it was shaped by family dynamics, living situations, and the transition each teen made during the personal journey.
Includes bibliographical references (page 179).
Keywords: Transgender youth -- Juvenile literature; Gender identity -- Juvenile literature; Transgenderism; Gender identity; Sex role